2019
DOI: 10.1001/jamanetworkopen.2019.1139
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Couple-Based HIV and Sexually Transmitted Infection Prevention Intervention for Men in Community Supervision Programs and Their Female Sexual Partners

Abstract: Key Points Question Is a 5-session prevention intervention for HIV and sexually transmitted infections effective in reducing sexual risk behaviors among men in a community supervision program and their main female sexual partners? Findings In this randomized clinical trial of 230 couples, participants randomized to the 5-session couple-based prevention intervention arm reported significantly fewer incidences of unprotected sex, fewer sexual partners, and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…Childhood adverse experiences consisted of a scale based on the Revised Inventory of Adverse Childhood Experiences summing 6 dichotomous variables. [36] (Questions measured 1) verbal (‘Before the age of 18 , has a parent or caregiver repeatedly ridiculed you , put you down , ignored you , or told you were no good ? ’) 2) sexual (Before the age of 17 , did anyone ever touch private parts of your body , made you touch their body , or made you have sex against your wishes ? )…”
Section: Methodsmentioning
confidence: 99%
“…Childhood adverse experiences consisted of a scale based on the Revised Inventory of Adverse Childhood Experiences summing 6 dichotomous variables. [36] (Questions measured 1) verbal (‘Before the age of 18 , has a parent or caregiver repeatedly ridiculed you , put you down , ignored you , or told you were no good ? ’) 2) sexual (Before the age of 17 , did anyone ever touch private parts of your body , made you touch their body , or made you have sex against your wishes ? )…”
Section: Methodsmentioning
confidence: 99%
“…Of the 32 studies [16][17][18][19][20][21][22][23][24][25][26][29][30][31][32][33][34][36][37][38][39][40]42,[44][45][46][47][48][49][50][51]91] that reported on condom use, 21 were individual-RCT and 11 were cluster-RCT, though two studies reported results from the same cluster-RCT [17,20]. The interventions included in these studies varied (Table 4).…”
Section: Condom Usementioning
confidence: 99%
“…Wechsberg and colleagues [49] found that South African women who received a gender-focused HIV prevention intervention in addition to HTS reported more condom use with a main partner compared to women who received only HTS. In an US RCT that enrolled individuals in community supervision programmes and their female sex partners, El-Bassel and colleagues [24] noted a significantly lower number of condomless sex acts with study partners and non-study partners for individuals randomized to multi-session risk-reduction counselling (more-intensive HTS) versus one-time counselling.…”
Section: Condom Usementioning
confidence: 99%
See 1 more Smart Citation
“…We advocate for well-designed programs to empower LBW to effectively negotiate prevention strategies with their migrant partners, such as condom use, and HIV testing. In fact, interventions that target couples have been found to be effective in preventing HIV and sexually transmitted diseases (El-Bassel et al, 2019;Jiwatram-Negrón & El-Bassel, 2014). These interventions have largely focused on building knowledge (i.e., sexually transmitted infections), enhancing skills (i.e., negotiation), and recommending approaches to preserving a healthy relationship.…”
Section: Mental and Reproductive Health Outcomesmentioning
confidence: 99%